Cognition and innovation - Sund, Kristian J., 1975-; Galavan, Robert; Brusoni, Stefano (New horizons in managerial and organizational cognition,, 2018)
Exploring the management of innovation is a largely interdisciplinary endeavour. It requires scholars to address problems from a variety of perspectives that include strategic, operational, technological and behavioural. The problem domain includes the management of innovation, technology strategy, research and development, information technologies, technology-based entrepreneurship, and the commercialization of scientific research. Behavioural theories of innovation have developed in multiple directions over the years, and this collection of chapters takes stock and provides examples of new developments at the intersection of innovation studies, and studies of managerial and organizational cognition.This is the third volume in the New Horizons in Managerial and Organizational Cognition series and comprises a collection of contributions that reflects the rich and encouraging developments at the intersection of cognition and innovation. The book explores the frontiers of socio-cognitive and socio-psychological research as it relates to innovation management and innovation processes. Major topics covered include attention, decision making, information processing, learning, cognitive frames, ecosystems and business model innovation, perceptual and interpretive processes, ethics and social dilemmas, power, and change.